Sistem Informasi Promosi dan Penjualan Pupuk, Beras dan Benih Berbasis Web - ester nababan; Filza Izzati; Rati Rahmadani; Lusiana Efrizoni (Computer Science and Information Technology, 2022)
Information systems have been widely used by several companies to switch manual systems to computerized systems. Online sales and promotions are currently growing rapidly. By utilizing web-based technology, the sales process can be carried out online and product promotion will have a wider range. PT.Sang Hyang Seri Pekanbaru is a company engaged in the agribusiness sector that collaborates with the Riau provincial agricultural office to distribute agricultural products. The company has its own production sites for rice, fertilizers and seeds. PT.Sang Hyang Seri Pekanbaru has problems in the sales business process which is still conventional (offline) where the company has to come directly to partners, so the process is limited and takes a long time. That way PT. Sang Hyang Seri Pekanbaru will lose competitiveness with companies that already use e-commerce. In this way the researchers propose a promotion and sales information system at PT.Sang Hyang Seri Pekanbaru with a waterfall system development model that the company can use as a forum for sales and promotion of agricultural products.